Complaint Analysis in Indonesian Language Using WPKE and RAKE Algorithm - Rini Wongso; Novita Hanafiah; Jaka Hartanto; Alexander Kevin; Charles Sutanto; Fiona Kesuma (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Social media provides convenience in communicating and can present two-way communication that allows companies to interact with their customer. Companies can use information obtained from social media to analyze how the communities respond to their services or products. The biggest challenge in processing information in social media like Twitter, is the unstructured sentences which could lead to incorrect text processing. However, this information is very important for companies’ survival. In this research, we proposed a method to extract keywords from tweets in Indonesian language, WPKE. We compared it with RAKE, an algorithm that is language independent and usually used for keyword extraction. Finally, we develop a method to do clustering to groups the topics of complaints with data set obtained from Twitter using the “komplain” hashtag. Our method can obtain the accuracy of 72.92% while RAKE can only obtain 35.42%.